Evaluation of the Virulence Gene Irp2 in Iraqi Patients of Urinary Tract Infections and Other Community-Acquired Illnesses - Hisham Mahmood, Shahad; Khalaf, Ilham Abdulhadi; Ghanem, Zainab J.; Baqer, Noor Nihad (HAYATI Journal of Biosciences, 2024)
A total of sixty-two isolates were tested to assess the presence of the irp2 gene in different isolates of Klebsiella pneumoniae. The isolates discussed in this study were obtained from patients who had acquired illnesses either within the hospital premises or in the surrounding vicinity. These isolates were sourced from three hospitals located in Baghdad, namely Al-Imam Ali, Al-Zaafaranya, and Ibin-Albady hospitals. One interesting thing about Klebsiella pneumoniae is that it makes siderophores, especially yersiniabactin. This is because of a gene that controls this trait. The application of DNA sequencing methodologies has facilitated the identification of the irp2 gene in 44% of Klebsiella pneumoniae. According to amino acid sequences and differentiation of nucleotide, the current work reports findings on the identification of the K. pneumoniae irp2 gene isolates collected from patients in Iraq. This event represents the initial recorded occurrence of such detection. The presence of this gene is considered an unconventional human pathogen. The aim is to explore the correlation between genetic analysis and the diagnosis of genetic variation by examining isolates documented in the global GenBank database (LC791754.1, LC791755.1, LC791756.1, LC791757.1, LC791758.1, LC791759.1, LC791760.1). Additionally, it seeks to provide insights into the magnitude of genetic variation observed within these isolates.